Performance Study of Bladeless Wind Turbine With Dimpled Mast - Esskindir Demeke Geto; A. Venkata Satyanarayana; Tesfaye Kebede Ali; Solomon Alemneh Adimass (Journal of Engineering)
The increasing demand for efficient and sustainable wind energy solutions has led to the development of vortex bladeless wind turbines (VBWTs), which utilize nonrotary masts and electromechanical components to harness wind energy through vortex-induced vibrations. Despite their potential, the aerodynamic performance of VBWTs remains limited by the mast’s geometry, presenting a critical research gap. This study investigates the impact of introducing shallow hexagonal dimples on the mast surface to enhance turbine performance. CAD models were developed with six dimple columns strategically placed at optimal azimuth locations. Using the k-ω SST turbulence model of Reynolds-averaged Navier–Stokes (RANS) equations, the aerodynamic force coefficients were evaluated. Additionally, vibration characteristics such as amplitude and frequency were estimated using a 2D cross-sectional model with Fast Fourier Transform (FFT) analysis. The experimental amplitudes and frequencies of the mast were estimated using a novel amplitude measuring stand. The findings reveal that the dimpled mast significantly improves lift and drag coefficients, vibration amplitudes, and overall power conversion efficiency. Compared to the base model, the dimpled mast achieves a fourfold increase in oscillation amplitude, reaching a maximum amplitude of 25.66 mm. These results demonstrate the effectiveness of surface engineering in optimizing VBWT performance.